2021
DOI: 10.1016/s2468-2667(21)00206-1
|View full text |Cite
|
Sign up to set email alerts
|

Deaths involving COVID-19 by self-reported disability status during the first two waves of the COVID-19 pandemic in England: a retrospective, population-based cohort study

Abstract: Background People with learning disabilities are at substantially increased risk of COVID-19 mortality, but evidence on risks of COVID-19 mortality for disabled people more generally is limited. We aimed to use population-level data to estimate the association between self-reported disability and death involving COVID-19 during the first two waves of the COVID-19 pandemic in England. MethodsWe conducted a retrospective, population-based cohort study of adults aged 30-100 years living in private households or c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 17 publications
1
22
0
Order By: Relevance
“…Between 1 September 2020 and 10 December 2021, 5,767,584 people (14.8% of the study population) living in England aged ≥10 years had tested positive for SARS-CoV-2, of which 46,484 (0.8%; 0.1% of the total study population) had an infection episode in both the second and third waves of the pandemic During the second wave, the largest differences in rates of testing positive for SARS-CoV-2 were observed for ethnicity; rates were highest in the Bangladeshi and Pakistani ethnic groups at 382. 4 and 373.8 per 100,000 person-weeks, respectively, and in the Chinese ethnic group, with 90.8 cases per 100,000 person-weeks. During the third wave, however, the White British ethnic group had the highest rate at 359.7 cases per 100,000 person-weeks (Table 2).…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Between 1 September 2020 and 10 December 2021, 5,767,584 people (14.8% of the study population) living in England aged ≥10 years had tested positive for SARS-CoV-2, of which 46,484 (0.8%; 0.1% of the total study population) had an infection episode in both the second and third waves of the pandemic During the second wave, the largest differences in rates of testing positive for SARS-CoV-2 were observed for ethnicity; rates were highest in the Bangladeshi and Pakistani ethnic groups at 382. 4 and 373.8 per 100,000 person-weeks, respectively, and in the Chinese ethnic group, with 90.8 cases per 100,000 person-weeks. During the third wave, however, the White British ethnic group had the highest rate at 359.7 cases per 100,000 person-weeks (Table 2).…”
Section: Resultsmentioning
confidence: 92%
“…Whilst the COVID-19 pandemic has affected all areas of the UK, some groups have been disproportionally affected. Rates of COVID-19 related hospitalisation and death have been higher among the elderly, people with pre-existing health conditions or disability [3] [4] [5], ethnic minority groups [6] [7] [8], some religious groups [9], people with low socio-economic status [10], and those living in care homes [11], large households [12], and deprived areas [13] [14] [15].…”
Section: Introductionmentioning
confidence: 99%
“…People with disabilities experience inequities in health access and outcomes, and these are potentially magnified with respect to coronavirus disease 2019 (COVID-19) (Shakespeare, Ndagire & Seketi 2021a ). Estimates from the UK show that at least 58% of deaths related to COVID-19 between January 2020 and February 2021 were amongst people with disabilities, although they only made up 17% of the population (Bosworth et al 2021 ). The increased risk of people with disabilities to COVID-19 mortality appears to occur for a combination of reasons, including higher risk of contracting the disease (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…People with disabilities (PwD) are disproportionately vulnerable to disasters; this includes but is not limited to negative mental health sequalae ( Stough, 2009 ; Stough and Kelman, 2018 ). A UK study during COVID-19 found that PwD are at greater risk of severe outcomes and death than the general population ( Bosworth et al, 2021 ). The global pandemic has disproportionately affected PwD, in terms of not just access to healthcare, but also to support services and networks, the ability to remain physically active, and their loneliness and mental health ( Czeisler et al, 2021 ; Jesus et al, 2021 ; Okoro et al, 2021 ; Wang et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%